Obstetrix - Kritzer, Naomi (Tordotcom, Tor Publishing Group, 2026)
"O Lord, deliver us. Doctor Liz has just been acquitted for performing the last abortion in North Dakota when she's kidnapped. They're not just any kidnappers, but a fundamentalist cult, deep in the rural west, without respect for law or decency, and in desperate need of an OB/GYN. Guarded, isolated, without access to the outside world, Liz nevertheless is treated with respect as the only doctor on the compound, but she is very aware of what happened to the last obstetrician they kidnapped. She must escape, and bring help to the girls trapped at the compound, if it's the last thing she does"-- Provided by publisher.